Efeitos da estação chuvosa na condição corporal e nos índices organossomáticos de duas espécies de anuros do gênero Leptodactylus Fitzinger, 1826 em área de Caatinga - Brito, Wenner Justino Bezerra de (2022)
In this study, individuals of two species, Leptodactylus fuscus and L. troglodytes, were used as a biological model to understand the reproductive and energetic dynamics of anurans that occur in Caatinga. The work was carried out in the Reserva Ecológica Verdes Pastos (REVP), located in the rural area of the municipality of São Mamede, Paraíba state, northeastern Brazil. Data on climatic factors for the region were acquired from the database of the Agência Executiva de Gestão de Águas da Paraíba (AESAPB). The collection of anurans was done by visual and auditory search during three months between February and April 2022, covering the reproductive season of the species. Thus, the gonads, liver and fat bodies were removed and measured and weighed. The biometric data obtained by weighing and measuring were body weight (WT), gonad weight (WG), liver weight (WL), fat body weight (WFB), and rostro-cloacal length (CRC). The values were then used for the calculations of the gonadosomatic, hepatosomatic and liposomatic ratios. The body condition index used for the present study was the total condition factor (K1), which was calculated for everyone. Based on the data, descriptive statistical treatment was performed; Student's t-test was used to show significant differences between the metrics; normality test; simple linear regression and correlation analysis. It was then found that L. fuscus and L. troglodytes are intrinsically associated with rainfall accumulation. The data suggested that during the rainy season both species modulate organosomatic characteristics due to the favorable breeding season, implying direct effects on the body condition of the individuals. It was also observed that both species tend to be vulnerable during the reproductive period and may contract infections by pathogens or become more susceptible to predation due to the decrease in energy as the accumulation of rainfall occurs. And when the liposomal ratio (RFB) and the total condition factor (K1) were compared, the species L. fuscus showed better fitness in relation to L. troglodytes, thus, even though both species share similar behavioral and physiological aspects, the individuals of L. fuscus showed a greater ability to tolerate the environment because they have better energy stores during the rainy season in Caatinga.